2019
DOI: 10.1111/scs.12739
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children with acute lymphoblastic leukaemia

Abstract: All co-authors have agreed to the submission and publication of this manuscript.QoL in children with ALL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…Zheng et al 16 conducted the largest study to date on HRQoL in children with ALL and found significant proportions of children with ALL experience impaired physical and emotional functioning beginning early in treatment and persisting. Other studies have found generally decreased HRQoL on therapy but improvement in scores as therapy progresses 26,28 . Our study supports and adds to the literature.…”
Section: Discussionsupporting
confidence: 86%
“…Zheng et al 16 conducted the largest study to date on HRQoL in children with ALL and found significant proportions of children with ALL experience impaired physical and emotional functioning beginning early in treatment and persisting. Other studies have found generally decreased HRQoL on therapy but improvement in scores as therapy progresses 26,28 . Our study supports and adds to the literature.…”
Section: Discussionsupporting
confidence: 86%
“…Given that the 5-year survival rate of ALL reaches up to 90%, the number of survivors has exponentially expanded throughout recent decades. The quality of life (QoL) of these long-term survivors can be compromised by sequelae [ 1 , 2 ], unpredictable health situations [ 3 ], depressive mood, fatigue, or weakness secondary to the ALL and its treatments [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of patients experience these problems shortly after treatment (i.e., <1 year post-treatment) [ 4 ]. Although QoL is often observed to recover or improve throughout their development, some patients might continue to experience mental or physical difficulties into adulthood [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the cross-sectional studies, two were related to the diagnostic phase (Magni et al, 1986; Ruccione et al, 1991), six were related to the initial/intermediate phases of treatment (i.e., the first year of treatment) (Iqbal & Siddiqui, 2002; Khazaeli et al, 2021; Sharan et al, 1995, 1999; Sint Nicolaas et al, 2016; Wang et al, 2017), and four were related to a later phase-maintenance (Daniel et al, 2018; Matthews et al, 2014; Rensen et al, 2020; Sherief et al, 2015). Two studies were related to any stage of active treatment (Irwanto et al, 2020; Jankowska-Polańska et al, 2020), and one was conducted from the initial treatment phases until maintenance (Steur et al, 2020). In addition, two studies were conducted from 6 months postdiagnosis to more than 12 months postdiagnosis (Bhattacharya et al, 2016) and 18 months postdiagnosis (Rao et al, 1992).…”
Section: Resultsmentioning
confidence: 99%